Pengaruh Ketersediaan Buku Ajar Madrasah Terhadap Minat Belajar SKI Pada Siswa/I Madrasah Aliyah Swasta Jam’iyah Mahmudiyah Tanjung Pura - Evi Apriani Nurmaini; Ahmad Sanusi Luqman; Muamar Al- Qadri (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The effect of the availability of Madrasah textbooks on interest in learning the history of Islamic culture in students of Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura. The subjects in this study were the 36 students of Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura. This research uses quantitative research methods. The location of the research was carried out in Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura, Tanjung Pura District, Langkat Regency. The implementation of this research was carried out in November-December 2021 until January 2022. The purpose of this study was to determine the effect of the availability of Madrasa textbooks on the interest in learning the history of Islamic culture in Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura students, what are the two variables? there is a significant relationship. To prove this, the researchers conducted a study conducted on 36 students of Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura who were used as research samples (random samples). Data collection tools are library research, observation, questionnaires and interviews. The results of the questionnaire were processed by tabulating the data to determine the frequency. Based on the discussion of research results in this study, it can be seen that the effect of the availability of Madrasah textbooks on students of Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura is very good (69.4%). While the interest in learning the history of Islamic culture in the students of Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura is good (69.4%). The results of the tabulation calculation between the influence of the availability of Madrasa textbooks on the interest in learning the history of Islamic culture in the students of Madrasah Aliyah Private Jam'iyah Mahmudiyah Tanjung Pura with a moderate or sufficient level of significance.